2010
DOI: 10.1007/s10482-010-9429-1
|View full text |Cite
|
Sign up to set email alerts
|

What does it take to be a plant pathogen: genomic insights from Streptomyces species

Abstract: Plant pathogenicity is rare in the genus Streptomyces, with only a dozen or so species possessing this trait out of the more than 900 species described. Nevertheless, such species have had a significant impact on agricultural economies throughout the world due to their ability to cause important crop diseases such as potato common scab, which is characterized by lesions that form on the potato tuber surface. All pathogenic species that cause common scab produce a family of phytotoxins called the thaxtomins, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 127 publications
(124 reference statements)
2
72
0
1
Order By: Relevance
“…Notably, the pathogenic species for which sequence information is available encode PecS, including the plant pathogens S. ipomoeae, Streptomyces scabiei, Streptomyces acidiscabies, and S. turgidiscabies and the human pathogen Streptomyces somaliensis (31)(32)(33)(34). The pathogenicity of Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the pathogenic species for which sequence information is available encode PecS, including the plant pathogens S. ipomoeae, Streptomyces scabiei, Streptomyces acidiscabies, and S. turgidiscabies and the human pathogen Streptomyces somaliensis (31)(32)(33)(34). The pathogenicity of Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…STTGS_ 50_ 00290 and STTGS_ 50_ 00280 were characterized as TxtA and TxtB, respectively, which catalyze the synthesis of the cellulose-synthesis-inhibiting virulence factor thaxtomin (Healy et al, 2000) and were reported to exist in many phytopathogenic Streptomyces species (Bignell et al, 2010a). Of the six NRPS gene clusters, with the exception of the txt cluster, three (STTGS_ 09_ 00680-STTGS_ 09_ 00690, STTGS_ 10_ 01580, and STTGS_ 07_ 02660) showed similarities to NRPSs in S. scabiei 87.22.…”
Section: Nrps Gene Clustersmentioning
confidence: 99%
“…While the presence of a coronafacic acid (CFA)-like biosynthetic cluster and a putative concanamycin biosynthetic cluster within the genome was previously reported (Bignell et al, 2010a, b), the other secondary metabolic gene clusters have not yet been surveyed. Genes from the CFA-like cluster were not detected in S. acidiscabies or S. turgidiscabies, and these two species also did not produce concanamycins (Bignell et al, 2010a). These results suggested that secondary metabolic gene clusters, except for txtABCD, found in S. scabiei 87.22 do not appear to be well conserved in other Streptomyces species.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The function of most of the Streptomyces pathogenome has still to be resolved but it does include genes spread through HGT that encode secreted proteins, transcriptional regulators and membrane transporters, as well as for secondary metabolite biosynthesis (Loria, Kers, & Joshi, 2006;Bignell, Huguet-Tapia, Joshi, Pettis, & Loria, 2010). S. acidiscabies and S. turgidiscabies are thought to be newly emergent pathogens with a limited geographical distribution.…”
Section: Mlsa Of Phytopathogenic Streptomyces Speciesmentioning
confidence: 99%